Measurement of zakat impact through sustainable livelihood impact assessment on Balai Ternak in Tanah Datar - Beik, Irfan Syauqi; Bahri, Efri Syamsul; Asmita, Budi; Fahrudin, Fahrudin (2019)
Purpose: This paper measures the impact of zakat on beneficiary mustahiq beneficiaries in Tanah Datar Animal Husbandry programs Design/methodology/approach: This research uses quantitative methods with a measurement model of Sustainability Livelihood Impact Assessment (SLIA). Findings: The results showed that the Tanah Datar Animal Husbandry program had quite an impact on the increase in Mustahik Community Assets. This is seen from the increase in 5 (five) SLIA assets with a variant value of 1.09 points. The highest increase occurred in Social Assets with a variant value of 1.25. Meanwhile, the lowest increase was in Natural Assets with a variant value of 0.93 points. For Financial Assets, there was an increase in changes with a variant value of 1.19, which shows the high impact of the Tanah Datar Animal Husbandry program on increasing the income of mustahik families. This increase was influenced by the sale of organic fertilizer and compost processed from goat manure. The aspect of vulnerability that can affect the Tanah Datar Livestock Center is a fairly high outbreak of livestock disease which results in the death of the mother and child during childbirth. Originality/value: Originality / value: The authenticity of this study is to assess the impact of zakat on the beneficiary's mustahik. Another new aspect of this research is the methodology that uses Sustainability Livelihood Impact Assessment (SLIA).